On Class Difference in Educational Aspirations and Educational Expectations: A CUCDS-Based Social Analysis - Bohan Yan; Ning Cai (Complexity)
Educational aspirations under an ideal state and educational expectations based on reality have an important impact on children’s academic development, but distinct differences between them exist. On the basis of distinguishing the differences between the two, using the national data of Tsinghua University’s China Urbanization and Child Development Survey (CUCDS), this article endeavors to explore the inequality of educational aspirations and expectations from the perspective of class and urban-rural areas, and lay out the influencing factors of educational aspirations, expectations, and the difference between them. It is found that Chinese parents generally have high aspirations for their children’s education. There is no distinct class difference in “high hopes for children’s bright future.” However, in the sense of educational expectations, there are distinct class differences, which are deeply rooted in socioeconomic status and closely related to education level, family type, family structure, and family economic status, as well as children’s academic performance.